Synthesis of arylselenide ethers by photoinduced reactions of selenobenzamide, selenourea and selenocyanate anions with aryl halides - Bouchet, Lydia María (2011)
Selenobenzamide (-SeCNH(Ph), 1), selenourea ( -SeCNH(NH2), 2) and selenocyanate (-SeCN, 3) anions afford areneselenolate ions (ArSe-) under photostimulation in the presence of tert-butoxide or 2-naphthoxide ions as electron donors (entrainment conditions) in DMSO. In a 'one-pot' procedure, ArSe- anions can be trapped by a subsequent aliphatic nucleophilic substitution giving aryl methyl selenides in good to excellent yields (67-100%). This simple approach is compatible with electron-donating and electron-withdrawing substituents, such as nitro and carbonyl groups. © 2010 Elsevier Ltd. All rights reserved.